KREATIVITAS BERBAHASA MELALUI EKSPLORASI GAYA BAHASA IKLAN PROMOSI SKINCARE DI MEDIA TIKTOK - Intan Putri Dwi Handayani; Dewi Kusumaningsih; Sukarno Sukarno; Pramudya Dhanabhrata (Universitas Negeri Makassar, 2023)
This study aims to describe the style of language and the meaning of the style of language used in the language of skincare promotional advertisements on TikTok media and how creative language is evident from the choice of language styles in skincare promotional advertisements on TikTok media. This study used descriptive qualitative method. The object of this research is the form of language style in the form of words or sentences. The data collected is in the form of language styles contained in skincare promotion advertisements on TikTok media. Data is transcribed from the video and converted into narrative sentences and/or dialogue. The data collection technique for this research is by documenting skincare promotional advertising videos on TikTok media. Source triangulation is used to examine several related sources to test the credibility of research data. The results of the study found that 11 skincare ad data on TikTok media contained language styles. The results consist of 9 styles of hyperbole, 3 styles of assonance, 1 style of metaphor, and 1 style of simile. As well as language creativity that arises from the use of language styles in skincare promotion advertisements on TikTok media.